2021
DOI: 10.5219/1518
|View full text |Cite
|
Sign up to set email alerts
|

Research of hop polyphenols impact on malt hopped wort aroma formation model experiments

Abstract: Currently, a lot of research is being done on the flavoring compounds of hops. However, much less attention has been paid to the aroma formation considering the hop polyphenol different groups by various methods at the wort hopping stage. Therefore, the main goal of the research is an impact of hopping conditions on the polyphenolic compounds, when the hop is extracted variously into both wort and water to better understand extraction conditions, mechanisms, and factors as well as aroma formation considering v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
1
0
3
Order By: Relevance
“…Полифенолы хмеля, как и другие соединения, отвечают за формирование вкусовых оттенков пива наряду с горькими α-кислотами, их изо-формами и эфирными смолами [2].…”
Section: аннотацияunclassified
“…Полифенолы хмеля, как и другие соединения, отвечают за формирование вкусовых оттенков пива наряду с горькими α-кислотами, их изо-формами и эфирными смолами [2].…”
Section: аннотацияunclassified
“…Along with bitter resins, polyphenol hop compounds are extracted, which form a phenol profile responsible for the stability of the colloidal system of beer [ 112 ]. Thus, it was found that amino acids of a hydrophilic nature (arginine, aspartic acid) contained in wort interact with hop catechins [ 113 ] through the decarboxylation of amino acid and detaching of catechin hydroxy groups to form a biogenic catechol amine, which leads to stabilization of hop polyphenols [ 114 ]. This fact makes the process of apoptosis induction in cancer cells a little clearer by inhibiting the activity of tumor necrosis factor α (TNF-α) with the participation of biogenic amine [ 115 ].…”
Section: The Beer’s “Body” Biomoleculesmentioning
confidence: 99%
“…Совсем недавно было установлено, что полифенолы хмелепродуктов влияют на образование вкуса и аромата в зависимости от количественного аминокислотного состава сусла, рН среды и времени и стадии внесения хмелепродуктов [13].…”
unclassified
“…На рисунке 1-2 представлено изменение профиля охмеленного сусла в зависимости от ряда факторов (момента внесения, типа хмеля и способа охмеления) на органолептический профиль [13]. Влияние изменения рН среды также было изучено (рисунок 3) и показало изменение пространственной конфигурации полифенольных соединений в зависимости от кислотности среды [13].…”
unclassified